In vitro cyclic compressive loads potentiate early osteogenic events in engineered bone tissue. Issue 8 (16th August 2016) - Ravichandran, Akhilandeshwari; Lim, Jing; Chong, Mark Seow Khoon; Wen, Feng; Liu, Yuchun; Pillay, Yaesshna T.; Chan, Jerry K. Y.; Teoh, Swee‐Hin
Abstract: Application of dynamic mechanical loads on bone and bone explants has been reported to enhance osteogenesis and mineralization. To date, published studies have incorporated a range of cyclic strains on 3D scaffolds and platforms to demonstrate the effect of mechanical loading on osteogenesis. However, most of the loading parameters used in these studies do not emulate the in vivo loading conditions. In addition, the scaffolds/platforms are not representative of the native osteoinductive environment of bone tissue and hence may not be entirely accurate to study the in vivo mechanical loading. We hypothesized that biomimicry of physiological loading will potentiate accelerated osteogenesis in bone grafts. In this study, we present a compression bioreactor system that applies cyclic compression to cellular grafts in a controlled manner. Polycaprolactone‐β Tricalcium Phosphate (PCL‐TCP) scaffolds seeded with Mesenchymal Stem Cells (MSC) were cyclically compressed in bioreactor for a period of 4 weeks at 1 Hz and physiological strain value of 0.22% for 4 h per day. Gene expression studies revealed increased expressions of osteogenesis‐related genes (Osteonectin and COL1A1) on day 7 of cyclic loading group relative to its static controls. Cyclic compression resulted in a 3.76‐fold increase in the activity of Alkaline Phosphatase (ALP) on day 14 when compared to its static group ( p  < 0.001). In addition, calcium deposition of cyclic loading group was found to attain saturation on day 14 (1.96 fold higher than its static scaffolds). The results suggested that cyclic, physiological compression of stem cell‐seeded scaffolds generated highly mineralized bone grafts. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 2366–2375, 2017.